If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -23 = -6n + -3(6n + -1) Reorder the terms: -23 + 2n = -6n + -3(6n + -1) Reorder the terms: -23 + 2n = -6n + -3(-1 + 6n) -23 + 2n = -6n + (-1 * -3 + 6n * -3) -23 + 2n = -6n + (3 + -18n) Reorder the terms: -23 + 2n = 3 + -6n + -18n Combine like terms: -6n + -18n = -24n -23 + 2n = 3 + -24n Solving -23 + 2n = 3 + -24n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '24n' to each side of the equation. -23 + 2n + 24n = 3 + -24n + 24n Combine like terms: 2n + 24n = 26n -23 + 26n = 3 + -24n + 24n Combine like terms: -24n + 24n = 0 -23 + 26n = 3 + 0 -23 + 26n = 3 Add '23' to each side of the equation. -23 + 23 + 26n = 3 + 23 Combine like terms: -23 + 23 = 0 0 + 26n = 3 + 23 26n = 3 + 23 Combine like terms: 3 + 23 = 26 26n = 26 Divide each side by '26'. n = 1 Simplifying n = 1
| 2-7(d-1)=3(d-2)-5(d-3) | | (150-2X)(100-2X)=0 | | 3x-6=20+4x | | 1.75p=9.25 | | -26-2b=-7(b+3) | | -[9x-(2x+4)]=-5-[4(3x-3)-3x] | | -15n=-5 | | -0.7=9.1 | | 16=d-12 | | x-2.25=-3 | | -5(-6k-1)=8k-39 | | 6x-2y+7=180 | | 40p+32=8p-192 | | 6x-12=10x-14 | | 24x-2x^2-6=0 | | x^2+x-4294967295=0 | | 8+2=2+5 | | 4a+19=2a-15 | | 24x-2x^2=6 | | x/3-10=-6 | | 6x-2y=172 | | 4za+19=2a-15 | | -7x-6=-4x-5x | | -5(2x+7)+3x=2x+12 | | 3v-1=5 | | -[9z-(12z+7)]=7+(2z+6) | | 42a^2-52a-30= | | 5x+2.1=-3.6 | | k-38=-3(1-2k) | | 6-(2y-7)=3-3y | | 3n+3=30 | | 69+2=84-3 |